The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1126/science.abe0690
|View full text |Cite
|
Sign up to set email alerts
|

Conserved genetic signatures parcellate cardinal spinal neuron classes into local and projection subsets

Abstract: Motor and sensory functions of the spinal cord are mediated by populations of cardinal neurons arising from separate progenitor lineages. However, each cardinal class is composed of multiple neuronal types with distinct molecular, anatomical, and physiological features, and there is not a unifying logic that systematically accounts for this diversity. We reasoned that the expansion of new neuronal types occurred in a stepwise manner analogous to animal speciation, and we explored this by defining transcriptomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 53 publications
(78 reference statements)
2
67
0
Order By: Relevance
“…Together, the data argue against sequential expression of these TFs during neuronal maturation because, in such a model, TFs with an early onset of expression would be specific for early maturation stages and would thus, contrary to our observations, expected to be labeled by EdU given at late developmental time points. Consistent with this interpretation, a recent study found similar birthdates for Zfhx3-and Neurod2-positive neurons in the perinatal spinal cord [41]. We therefore conclude that these TFs comprise a temporal code and label distinct subsets of neurons based on their time point of birth in the spinal cord.…”
Section: Edu Birthdating Reveals a Temporal Tf Code In Spinal Cord Neuronssupporting
confidence: 88%
See 1 more Smart Citation
“…Together, the data argue against sequential expression of these TFs during neuronal maturation because, in such a model, TFs with an early onset of expression would be specific for early maturation stages and would thus, contrary to our observations, expected to be labeled by EdU given at late developmental time points. Consistent with this interpretation, a recent study found similar birthdates for Zfhx3-and Neurod2-positive neurons in the perinatal spinal cord [41]. We therefore conclude that these TFs comprise a temporal code and label distinct subsets of neurons based on their time point of birth in the spinal cord.…”
Section: Edu Birthdating Reveals a Temporal Tf Code In Spinal Cord Neuronssupporting
confidence: 88%
“…Neurod2/6 control neuropeptide expression in inhibitory neurons in the dorsal horns of the spinal cord [40], and characterization of V2a neuron heterogeneity revealed that Zfhx3 and Neurod2/Nfib divide this neuronal class into a lateral and medial population [29]. Recent evidence further suggests that Zfhx3 and Nfib/Neurod2 partition neurons in the spinal cord into long-range projection and local interneurons [41]. Similar to the spinal cord, Onecut, Pou2f2, and Nfi-TFs label early and late-born neuronal subtypes in the retina and are required for their generation [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…We noted that this cluster expressed a diverse set of genes associated with ascending projection neurons from the lumbar spinal cord to the brain, including Lypd1, Tacr1, Zfhx3, Pou6f2, Tac1, Syt4, Fam19a2, Scn9a, Nms, and Pde8b (Fig. 3e) [17][18][19][20][21] . In particular, the expression of Slc17a6 (vGlut2), Zfhx3, and Pou6f2 suggested that some of these cells were likely excitatory neurons that resided in the lateral part of deep dorsal or ventral horn [21][22][23] .…”
Section: Rare Populations Of Spinal Neurons Induce a Gene Expression Signature Of Regenerationmentioning
confidence: 96%
“…3e) [17][18][19][20][21] . In particular, the expression of Slc17a6 (vGlut2), Zfhx3, and Pou6f2 suggested that some of these cells were likely excitatory neurons that resided in the lateral part of deep dorsal or ventral horn [21][22][23] . Together, these data suggest that a heterogeneous but rare set of ascending spinal cord neurons induce a RAG signature after contusion injury.…”
Section: Rare Populations Of Spinal Neurons Induce a Gene Expression Signature Of Regenerationmentioning
confidence: 99%
“…These molecular codes may serve not only as markers, but also provide insights into how precise axon targeting and neural circuit patterning is achieved. This principle seems to be applicable to other neuronal types 81 and adult MNs 26 . Unexpectedly, either by means of trypsin- or papain-based disscociation approaches, we acquired equivalent numbers of MMC (2354 cells) and LMC (2248 cells) MNs, which is inconsistent with the population ratio of brachial LMC to MMC MNs (4:1) in E13.5 mouse embryos 82 .…”
Section: Discussionmentioning
confidence: 95%